Pengaruh Model Pembelajaran Guided Inquiry Berbasis Pictorial Riddle Dalam Meningkatkan Berpikir Kreatif Siswa pada Pembelajaran IPA di SDN Gudang - Titin Fahmi Qoyyimah; Oktian Fajar Nugroho (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aims to see the effect of the pictorial riddle-based guided inquiry learning model in improving students' creative thinking. This study uses a pre-experimental design research method in the form of one group pretest-posttest design. This study used purposive sampling where the sample was selected on the consideration of the researcher, the sample used was 28 fourth grade students at SDN Gudang. The instrument of this research is the observation of the syntax of the guided inquiry learning model based on pictorial riddles, the observation of creative thinking, and the essay test. The results of this study stated that the average value of the pretest was 21.75 and the average value of the posttest was 31.11. The significance value at the pretest is 0.107 and the significance value at the posttest is 0.200, which means that each significance value is more than 0.05. Hypothesis testing with t-test obtained a significance value of 0.000 <0.005, which means that there is a significant difference. So it can be stated that the pictorial riddle-based guided inquiry learning model has a significant positive effect on students' creative thinking.